Investigation the influences of water-extractable and water-unextractable arabinoxylan on the quality of whole wheat you-tiao and its mechanism. (30th August 2022) - Sun, Juan; Zhou, Ruoxin; Qian, Haifeng; Li, Yan; Zhang, Hui; Qi, Xiguang; Wang, Li
Highlights: Water-extractable arabinoxylan increased you-tiao's specific volume and oil content. Water-extractable arabinoxylan inhibited the thermal aggregation of gluten proteins. Water-unextractable arabinoxylan hindered the expansion of the gluten network. Water-extractable arabinoxylan reduced the contents of β-sheet and the random coil. Water-extractable arabinoxylan improved the quality of whole-wheat youtiao. Abstract: This research aimed to investigate the effects of water-extractable arabinoxylan (WEAX) and water-unextractable arabinoxylan (WUAX) on the quality of you-tiao. In this work, the interactions between different amounts of AX and wheat gluten were extensively evaluated during frying treatment. The results showed that WEAX impaired the surface hydrophobicity of gluten and improved its solubility, while WUAX had the opposite effect. The fluorescence spectra revealed that WEAX and WUAX changed the conformation of gluten molecules. Besides, chemical interaction measurement indicated that WEAX and WUAX prevented the formation of partial disulfide bonds and inhibited the thermal aggregation of gluten proteins. In summary, the results indicated that WEAX partly improved the properties of you-tiao. Meanwhile, WUAX reduced the dough's oil content and specific volume, resulting in you-tiao with poor quality.